Menumbuhkan Generasi Qur’ani: Optimalisasi Program Maghrib Mengaji untuk Anak Bangsa - Patimah Sari; Rahmi Seri Hanida; Aisyaturridho Aisyaturridho; Anita Khairani; Tiara Adelina; Lailatul Jannah (Medan Resource Center, 2024)
This study evaluates the implementation of the Maghrib Mengaji program in Jorong Permukiman Baru II, Koto Balingka District, with a focus on children as an effort to deepen religious knowledge and cultivate a generation with noble character. The program aims to revive the tradition of reading the Qur'an after Maghrib prayer, in response to the shift in children's habits, who are now more often engaged with gadgets and television. By fostering deeper religious understanding, enhancing Qur'an reading skills, and reducing the negative influence of electronic media, the program seeks to create positive change. The study was conducted using a descriptive qualitative approach through observation, interviews, and documentation, with triangulation applied to ensure data validity. The research location included Masjid Al-Muhajrin and TPA Al-Muhajrin, with informants consisting of Qur'an teachers and religious figures actively involved in the program. The findings indicate that the Maghrib Mengaji program has successfully increased children's interest in reading the Qur'an and their frequency of visits to the mosque. However, several challenges remain, particularly in addressing reading difficulties and understanding tajweed, as well as attracting the interest of children who are more drawn to electronic media. With improved teaching methods and the provision of more engaging materials, it is hoped that the program can be more effective in enhancing Qur'an reading skills and supporting the formation of a Qur'anic generation. Positive community support also shows that the program has succeeded in creating a more vibrant atmosphere at the mosque, although continuous evaluation is needed to achieve optimal results.